Study on Potassium Bearing Minerals in Sand Fraction Through X-Ray Diffraction Techniques - Kaliramana, R.S.; Pannu, B.S.; Singh, J.P. (Asian Journal of Chemistry, 2012)
The potassic feldspar, mica were the prime sources of potassium bearing minerals indentified in these soils. The feldspar and mica were concentrated mainly occurred in the coarse fraction of the soils. The soil of aeolian plain and rugged hilly terrain of Aravalli range of semi-arid region contained high amount of feldspar than mica, but the reverse trend was observed in rest of the soils of this region. The difference in the mineralogical composition within the soils of semi-arid region was found to be originated from the source of alluvium and parent rocks.